Mandatory Infant Vaccinations in France During the COVID-19 Pandemic in 2020 - Taine, Marion; Offredo, Lucile; Drouin, Jérôme; Toubiana, Julie; Weill, Alain; Zureik, Mahmoud; Dray-Spira, Rosemary (Frontiers in Pediatrics, 2021)
Objectives: To describe changes in the dispensation of 11 mandatory vaccines among infants during the COVID-19 pandemic in France in 2020, considering priming doses and boosters separately. Methods: Using the French national health database, all dispensations of priming doses and boosters of 11 mandatory vaccines (penta/hexavalent, measles mumps rubella [MMR], meningococcal conjugate type-C [Men-C-C], 13-valent pneumococcal conjugate [PCV13]) for infants aged≤24 months were aggregated by 4-week periods in 2020. Expected counts in 2020 were estimated based on counts in 2019 weighted by a ratio considering the level of vaccine dispensation before the pandemic onset in 2020. Relative differences (RDs) and their 95% confidence intervals (CIs) were computed to compare observed and expected counts during the first and second lockdown, and period in-between. Results: During the first 4 weeks of the lockdown, as compared with expected numbers, observed priming dose counts substantially decreased (RD: from -5.7% (95% CI -6.1; -5.2) for penta/hexavalent to -25.2% (95% CI -25.6;-24.8) for MMR) as well as for boosters (RD: from -15.3% (95% CI -15.9; -14.7) for penta/hexavalent to -20.7% (95% CI -21.3; -20.2) for Men-C-C). Priming doses and boosters remained slightly below the expected afterwards. Over the year 2020, MMR priming doses and Men-C-C booster had the highest shortfalls (N=84,893 and 72,498, respectively). Conclusions: This study provides evidence of a lack of vaccination catch-up after the first lockdown and a persistent shortfall in infant vaccines after the first 10 months of the COVID-19 pandemic in France, especially for MMR priming doses and Men-C-C booster.